Why Word Learning is not Fast - Munro, Natalie; Baker, Elise; Mcgregor, Karla; Docking, Kimberley; Arciuli, Joanne (Frontiers in Psychology, 2012)
Upon fast mapping, children rarely retain new words even over intervals as short as five minutes. In this study, we asked whether the memory process of encoding or consolidation is the bottleneck to retention. Forty-nine children, mean age 33 months, were exposed to eight 2-or-3-syllable nonce neighbors of words in their existing lexicons. Didactic training consisted of six exposures to each word in the context of its referent, an unfamiliar toy. Productions were elicited four times: immediately following the examiner’s model, and at 1-minute-, 5-minute-, and multiday retention intervals. At the final two intervals, the examiner said the first syllable and provided a beat gesture highlighting target word length in syllables as a cue following any erred production. The children were highly accurate at immediate posttest. Accuracy fell sharply over the 1-minute retention interval and again after an additional 5 minutes. Performance then stabilized such that the 5-minute and multiday posttests yielded comparable performance. Given this time course, we conclude that it was not the post-encoding process of consolidation but the process of encoding itself that presented the primary bottleneck to retention. Patterns of errors and responses to cueing upon error suggested that word forms were particularly vulnerable to partial decay during the time course of encoding.